The impact of quality management practices on organization performance at Kuching - Chong, Mei Chin (Universiti Malaysia Sarawak, UNIMAS, 2009)
The main aim of this study is to explore the relationship between quality management practices (leadership, continuous improvement, training and working culture) and their impact toward organization performance .A total of 140 sets of structured questionnaires were distributed to SMI Company in variety of industries and enterprise ownership which located in Kuching, only 52.14% of it, which is 73, were returned. The collected data was analyzed based on frequency, factor analysis, reliability, Person Correlation Coefficient, Regression, means and standard deviation. The findings of the study showed that continuous improvement and working culture had strong relationship with organization performance while leadership and training showed a weak relationship with organization performance.